An open‐label study of anidulafungin for the treatment of candidaemia/invasive candidiasis in Latin America. Issue 1 (26th May 2013) - Nucci, Marcio; Colombo, Arnaldo L.; Petti, Marco; Magana, Martin; Abreu, Paula; Schlamm, Haran T.; Sanchez, Sonia P.
Summary Incidence and mortality of candidaemia/invasive candidiasis (C/IC) is relatively high in Latin America versus North America and Europe. To assess efficacy and safety of intravenous (IV) anidulafungin in Latin American adults with documented C/IC. All patients in this open‐label study received initial IV anidulafungin with optional step‐down to oral voriconazole after 5 days; total treatment duration was 14–42 days. The primary endpoint was global response (clinical + microbiological response) at end of treatment (EOT); missing/indeterminate responses were failures. The study enrolled 54 patients; 44 had confirmed C/IC within 96 h before study entry and comprised the modified intent‐to‐treat population. Global response at EOT was 59.1% (95% CI: 44.6, 73.6), with 13 missing/indeterminate assessments. Thirty‐day all‐cause mortality was 43.1%. Fourteen patients (31.8%) were able to step‐down to oral voriconazole; these patients had lower baseline acute physiological assessment and chronic health evaluation (APACHE) II scores and were less likely to have solid tumours or previous abdominal surgery. Anidulafungin was generally well tolerated with few treatment‐related adverse events. Anidulafungin was associated with relatively low response rates influenced by a high rate of missing/indeterminate assessments and mortality comparable to other recent candidaemia studies in Latin America. In a subset of patients with lower APACHE II scores, short‐course anidulafungin followed by oral voriconazole was successful.